Power dynamics influence resilience to shocks: evidence from Bangladesh - Zack Guido; Timothy J. Finan; Mehrul Islam; Fatima Jahan Seema; Nayeem Hasan; Saima Akter; Baishakhi Ghosh; Faysal Ahmed Shovo; James Soren (Global Environmental Change Advances)
Resilience has gained influence as an organizing principal for development in recent years. It offers a logic that places development progress on the ability of individuals or groups to maintain well-being, and possibly transform it, despite social and environmental shocks. Although there has been substantial research on the determinants of resilience, a gap in understanding exists about how power dynamics affect resilience and how resilience interventions can address power. This research study explores the links between power and resilience within highly vulnerable communities where development interventions have had a long presence. We present empirical results from community-based research conducted in eight rural northern Bangladesh communities. Our analysis is presented in three steps. First, we show the various ways people contend with shocks, and we group these local activities into common resilience strategies. We then show evidence of change in the traditional exercise of power expressed as increased agency (power-to) and reduced constraints and restrictions (power-over). Finally, we show different pathways by which the changes in power affect resilience strategies, concluding that shifts towards more equitable power relations enhance resilience capacities. We discuss the implications of these results for designing resilience interventions and integrating power into resilience studies.150 Word SummaryResilience has become influential as an organizing principal for sustainable development, placing development progress on the ability of individuals or groups to maintain well-being or transform it despite social and environmental shocks. Resilience, however, has focused on material aspects of development and not adequately addressed how power dynamics affect resilience and how resilience interventions can address power. This study present results on the relationships between power and resilience using community-based research in eight rural Bangladesh communities. The study documents the ways people contend with shocks, presents evidence of change in the exercise of power expressed as increased agency (power-to) and reduced constraints and restrictions (power-over), and show pathways by which changes in power affect resilience. We discuss how development programming can use power analyses to design of interventions and evaluated their impacts. We conclude that shifts towards more equitable power relations enhance resilience capacities and, thus, development goals.